Identifying the Spatiotemporal Transitions and Future Development of a Grazed Mediterranean Landscape of South Greece - Dimitrios Chouvardas; Maria Karatassiou; Afroditi Stergiou; Garyfallia Chrysanthopoulou (Land, 2022)
Spatiotemporal changes over previous decades in grazed Mediterranean landscapes have taken the form of woody plant encroachment in open areas (e.g., grasslands, open shrublands, silvopastoral areas), altering its structure and diversity. Demographic and socioeconomic changes have played a significant role in landscape transformations, mainly by causing the abandonment of traditional management practices such as pastoral activities, wood harvesting, and agricultural practices in marginal lands. This study aimed to quantify and evaluate the spatiotemporal changes in a typical grazed Mediterranean landscape of Mount Zireia during 1945–2020, and to investigate the effect of these changes on the future development (2020–2040) of land use/land cover (LULC) types. Cartographic materials such as aerial orthophotos from 1945, land use maps of 1960, Corine Land Cover of 2018, and recent satellite images were processed with ArcGIS software. To estimate the future projection trends of LULC types, logistic regression analyses were considered in the framework of CLUE modeling. The results indicated that the strongest trend of spatiotemporal changes were forest expansion in open areas, and grasslands reduction, suggesting that the LULC types that were mainly affected were forest, grasslands, and silvopastoral areas. Future development prediction showed that forests will most probably continue to expand over grassland and silvopastoral areas, holding a high dynamic of expansion into abandoned areas. The reduction in grasslands and silvopastoral areas, independent of environment and biodiversity implications, represents a major threat to sustainable livestock husbandry based on natural grazing resources.